Eksplorasi Pengaruh Film Kimi no Nawa Terhadap Minat Berkunjung Wisatawan Indonesia Untuk Berkunjung ke Jepang - Logenie Salwas Sabina; Dina Hariani (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
With the advancement of technology, one of the newest methods of promoting tourism is through the use of movies. However, in Indonesia, tourism promotion using films is still not widely used. Kimi no Nawa film was first released in Japan in 2016. Kimi no Nawa film uses real locations in Japan and makes these locations the background of the film. As a result, more people visit the places that serve as the backdrop for the Kimi no Nawa movie. This study uses a quantitative methodology with the aim of determining effect film tourism of Kimi no Nawa film on Indonesian tourist interest in visiting Japan. Data analysis utilizes a questionnaire processed with the help of SPSS version 25. The researcher managed to get 160 respondents. The results of the t-statistic test show a value of 0.000 < 0.05, which means that there is a positive effect from film tourism of Kimi no Nawa film to Indonesian tourist interest in visiting Japan.. The film tourism variable is considered to influence the tourist interest variable by 45.7%, which can be interpreted as having a significant effect